If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 6x + -3y + -5x + 4x = 0 Reorder the terms: 6x + -5x + 4x + 5y + -3y = 0 Combine like terms: 6x + -5x = 1x 1x + 4x + 5y + -3y = 0 Combine like terms: 1x + 4x = 5x 5x + 5y + -3y = 0 Combine like terms: 5y + -3y = 2y 5x + 2y = 0 Solving 5x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 5x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 5x + 0 = 0 + -2y 5x = 0 + -2y Remove the zero: 5x = -2y Divide each side by '5'. x = -0.4y Simplifying x = -0.4y
| 5y+6x-3y-5y+4x= | | 15m-9=21 | | -2(x-8)=(6x+4)-8 | | 3.45x+2.5y=52 | | 2r-5=1r | | -2x(x-8)=(6x+4)-8 | | -6r-10s+8r+4s-6= | | x^2+2x=89 | | 3x^4+9x^3-25x^2+15x-50=0 | | 2(5+-.5y)+y=10 | | 9y-2+9y=6 | | 18=-6-x | | Y=6x^7-2cosx | | =12v^4-8v^3 | | 7t-4.6=10.1 | | 3(xy+w*w)+2xy-2w*2w= | | 9w-18+5w+2=180 | | 9.5+p-6.8=7.3 | | -5s+9=-6 | | (5y+5)-5y=5 | | 15g-3(4g-6)=3g+9-9g | | 6+2x=4x-2 | | 2x+1=10x-3(x-1) | | 3y^2-15y=12 | | x^2+x-80=0 | | 6y+7=5y-5 | | 4a+2b-3-6a-5b= | | 5.5y=71.5 | | 7-6a=7a | | -3(4y-2)-y=-3(y-5) | | -2x^2+6x+8=0 | | 3x+2(x+3)=31 |